2005
DOI: 10.1159/000085172
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Ischemic Events in Patients with Advanced Lung or Prostate Cancer

Abstract: Conventional stroke risks are thought responsible for most cerebral ischemic events (CIE) in adult cancer patients. Also suspected as a risk is cisplatin chemotherapy, alone or in combination with tumor angiogenesis inhibitor. We investigated whether treatment or tumor characteristics, independently of conventional stroke risks, are associated with CIE in a retrospective cohort study of 1,559 patients with advanced non-small cell lung cancer or hormone-refractory prostate cancer followed during 3 clinical tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…An extensive analysis of ischaemic stroke after chemotherapy, in a series of 10,963 patients (93), concluded that the risk for stroke was predicted by the use of cisplatin-based chemotherapy and not by the histological type of cancer. Other studies did not reach this conclusion (18). Generally, the risk of chemotherapy-induced stroke seems low (94), but no systematic, drug-specific conclusion can be drawn up till now.…”
Section: Therapy-relatedmentioning
confidence: 96%
See 1 more Smart Citation
“…An extensive analysis of ischaemic stroke after chemotherapy, in a series of 10,963 patients (93), concluded that the risk for stroke was predicted by the use of cisplatin-based chemotherapy and not by the histological type of cancer. Other studies did not reach this conclusion (18). Generally, the risk of chemotherapy-induced stroke seems low (94), but no systematic, drug-specific conclusion can be drawn up till now.…”
Section: Therapy-relatedmentioning
confidence: 96%
“…Myxoma or other heart tumours (14-17) as well as lung tumours can be the source of embolism into the brain (18)(19)(20). The occlusion of a cerebral vessel can either cause an ischaemic stroke or give rise to arterial neoplastic aneurysms (21,22).…”
Section: Tumour Relatedmentioning
confidence: 99%
“…[1][2][3][4][5] The exact mechanism of this phenomenon is not clearly defined, however tumor cells can directly and indirectly enhance activation of the coagulation cascade. [1][2][3][4][5] The exact mechanism of this phenomenon is not clearly defined, however tumor cells can directly and indirectly enhance activation of the coagulation cascade.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] If cerebral infarction occurs in patients with multiple lesions of unknown cause, an underlying malignancy should be considered. However, it is rare that cerebral infarction presents as the first manifestation of an underlying or undiagnosed malignancy.…”
mentioning
confidence: 99%
“…Conventional stroke risk factors such as diabetes and hypertension correlated with stroke and TIA but did not meet significance in this study. The extent of the malignancy was more predictive, emphasizing the link between cancer and stroke [4].…”
Section: Co-morbidity Of Cancer and Cerebrovascular Diseasementioning
confidence: 98%